Assessment for the passage of tylosin into the milk of Anatolian buffaloes - ACAROZ, U; KUCUKKURT, I; INCE, S; ARSLAN-ACAROZ, D; GURLER, Z; ERYAVUZ, A (Journal of the Hellenic Veterinary Medical Society, 2021)
Tylosin is a broad-spectrum macrolide antibiotic commonly employed in veterinary medicine to treat bacterial infections. The present study assessed the milk-passage patterns of tylosin up to the 16th milking after a single intramuscular injection at the dose of 10 mg/kg/b.w. to Anatolian buffaloes. The residue levels of tylosin in milk samples of each animal were analysed by LC-MS/MS. The detection and determination limits of the employed method were 0.19 μg/kg and 0.64 μg/kg, respectively. The highest level of tylosin was found to be at the second milking. At the ninth milking, tylosin residue level decreased under the maximum residue limit of 50 μg/kg. Additionally, the employed LC-MS/MS method is used to assess tylosin residue in 40 milk samples and all of the samples were found to be tylosin free. In conclusion, this study determined the milk passaged levels of tylosin into milk of Anatolian buffaloes using an LC-MS/MS method.